2014
DOI: 10.1007/s10549-014-2983-x
|View full text |Cite
|
Sign up to set email alerts
|

Two histopathologically different diseases: hormone receptor-positive and hormone receptor-negative tumors in HER2-positive breast cancer

Abstract: The clinical behavior of human epidermal growth factor 2 (HER2)-positive breast cancer, including pathologic complete response rate and pattern of relapse and metastasis, differs substantially according to hormone receptor (HR) status. We investigated various histopathologic features of HER2-positive breast cancer and their correlation with HR status. We retrospectively analyzed tumors of 450 HER2-positive breast cancer patients treated with chemotherapy and 1 year of trastuzumab. HR-/HER2+ tumors showed highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
34
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 29 publications
8
34
1
1
Order By: Relevance
“…Moreover, different clinical behaviors and histopathologic characteristics of HR+/HER2+ breast cancers and HR–/HER2+ breast cancers have been reported [28,29]. In this study, we found that HR–/HER2+ breast cancers were significantly associated with a higher histologic grade, higher nuclear grade, and abundant amount of TILs when compared to HR+/HER2+ breast cancers, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, different clinical behaviors and histopathologic characteristics of HR+/HER2+ breast cancers and HR–/HER2+ breast cancers have been reported [28,29]. In this study, we found that HR–/HER2+ breast cancers were significantly associated with a higher histologic grade, higher nuclear grade, and abundant amount of TILs when compared to HR+/HER2+ breast cancers, consistent with previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Biological behaviors and prognoses of BC with different molecular phenotypes are different [26]. The luminal type was proved to be well differentiated with more of histological grade 1, small size, and negative axillary lymph node [26,27], while HER-2 enriched type and TNBC were considered to be poorly differentiated with higher histological grades, larger tumors, greater lymph involvements and more advanced stages [27,28]. Furthermore, some researches investigated the relationships between the subtypes of BC and distant metastases [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…We previously analyzed surgically resected, HER2-positive breast cancers from patients treated with adjuvant chemotherapy and trastuzumab and found that hormone receptor-negative/HER2positive (HR−/HER2+) tumors had more diffuse and intense lymphocytic infiltration, a higher nuclear grade, less tubule formation, a higher histologic grade, more frequent apocrine features, stronger HER2 immunohistochemical staining, a higher average HER2 copy number and HER2/CEP17 ratio, the absence of HER2 genetic heterogeneity, and more p53 expression than hormone receptor-positive/HER2-positive (HR+/HER2+) tumors. 1 HR-/HER2+ tumors also have a higher pathologically complete response rate to neoadjuvant systemic therapy than HR+/HER2+ tumors, and the patterns of relapse, metastatic spread, and patient survival also differ between these subtypes. [2][3][4] The prognostic and predictive values of tumor-infiltrating lymphocytes (TILs) have been determined for breast cancer.…”
mentioning
confidence: 99%